Surgical Plume and Its Implications: A Review of the Risk and Barriers to a Safe Workplace - Tan, Eunice; Russell, Kylie (Operating Room Nurses Association of Canada Journal, 2019)
Every year thousands of health care professionals worldwide are exposed to surgical smoke. There is evidence that this smoke consists of toxic gases, pathogens and particulate matter that is a hazard for patients and the perioperative team. Past research indicates that perioperative staff inconsistently comply with smoke evacuation recommendations. The aim of this study was to identify, review and discuss the issues related to surgical plume and its implications for patients and perioperative staff. The findings of this review relate to surgical smoke content, its risks to the health of the perioperative staff, preventative measures, infection control measures, compliance with smoke evacuation systems, staff knowledge and barriers to implementing smoke evacuation practices. Of particular importance, the literature indicated that strong support from management and the implementation of regular staff education could improve practice for the management of surgical plume in the operating theatre.